Tracing the primary production location of core-formed glass vessels, Mediterranean Group I. (February 2016) - Blomme, Annelore; Elsen, Jan; Brems, Dieter; Shortland, Andrew; Dotsika, Elissavet; Degryse, Patrick
Abstract: Core-formed glass vessels of Mediterranean Group I were produced in the Mediterranean area between the sixth and fourth centuries BC. Indirect archaeological arguments have pointed to Rhodes as the primary glassmaking centre for these vessels. By comparing the elemental composition of hypothetical glasses produced from sand raw materials collected along the coastline of Rhodes to the reduced base glass composition of the core-formed vessels, it can be suggested that such sands are unsuitable for the production of these ancient glasses. Other locations in the Aegean area, i.e. Crete, Corinthia and central Macedonia, can also be largely excluded. A primary Syro-Palestinian provenance is more likely, based on the similarities in elemental and strontium/neodymium isotopic composition between the Mediterranean Group I glass vessels and raw glass chunks and sand raw materials originating from the Levant. Highlights: This study examines the origin of core-formed glass vessels, Mediterranean Group I (sixth to fourth century BC). Geochemical and isotopic analyses are performed on several glass and sand samples. The hypothetical glass composition of each sand sample was compared with the average vessel base glass composition. Rhodes and other locations in the Aegean area can be excluded as primary production place.